(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
The objective of this article is to base a pedagogical conception for the management of the University Extension from the community socio-cultural project in the initial training of teachers at the University of Ciego de Ávila Máximo Gómez Báez. It is a qualitative research, developed through a process of systematization of the practice. Theoretical level methods,critical-reflexive observations of reality, documentary analysis and socialization workshops were used. The sample, selected by a non-probabilistic criterion and for convenience, is made up of 36 teachers from different pedagogical careers. Was designed a pedagogical conception for the management of the University Extension in the initial training of the Bachelor of Education; this is distinguished by the relationship between its conceptual and procedural dimensions and enriches the theoretical-methodological support for the management of University Extension from the curricular conception.